Pemberitaan Isu Terorisme Pada Media di Indonesia: Media Kompas.com dan Voa-Islam.com dalam Peristiwa Serangan Paris November 2015 - Renita Novitasari Putri; Zarmansyah Zarmansyah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Terrorism is an issue that has grown for a long time and is now a concern to the world community. This comes after what is being reported by the media can form a public perception or opinion. The amount of media influence on the public is supported also by technological developments in the media that currently raise the speed of delivery and its actuality through online media. Online media in Indonesia itself has many kinds, such as Kompas.com and VOA-islam.com which have two different backgrounds. Using the qualitative method of interviewing, framing analysis in agenda setting theory and public opinion as supporting theory, this research shows that both media were covering the Paris attacks in November with different methods and points of view. This research has proof that every media will cover an event according to the ideology and characteristic (mission and vision) respectively depending on the editor of the media, including in the selection of referrals and foreign media as a comparison